An environmentally friendly technology of disassembling electronic components from waste printed circuit boards. (July 2016) - Wang, Jianbo; Guo, Jie; Xu, Zhenming
Graphical abstract: Highlights: Methods to recycle WPCBs would be more efficient if ECs were disassembled firstly. LOTs should be removed firstly from TV-WPCBs. ECs could be disassembled automatically from PC-WPCBs. Abstract: Electronic components (ECs) disassembling from waste printed circuit boards (WPCBs) is the first and essential step in WPCBs recycling chain. Over the past decades, primitive methods like simply heating WPCBs on a coal-heated plate to melt solders are dominated in practice, causing serious environmental pollution and also putting a real threat to the human health. In order to solve this problem, in this article, an automatic system in pilot-scale for ECs disassembling from WPCBs is designed, manufactured, and investigated. This system contains two parts: ECs automatic disassembly and off-gas purification. Meanwhile, WPCBs from television (i.e., TV-WPCBs) and personal computer (i.e., PC-WPCBs) are used for disassembling tests, respectively. When the disassembling temperature, rotating speed, and incubation time are 265 ± 5 °C, 10 rpm, and 8 min, respectively, the solder can be completely removed from both TV-WPCBs and PC-WPCBs. No pollutant is discharged from this system. Finally, the disassembling procedures for ECs from both TV-WPCBs and PC-WPCBs are suggested to promote WPCBs disassembling in an environment-friendly way, without threaten the environment and human health.